Long-Range Real Migration of Implantable Cardioverter Defibrillator Lead - Keyser, Andreas; Brodoefel, Harald; Schmid, Christof (The Thoracic and Cardiovascular Surgeon Reports, 2016)
The need for pacemaker and implantable cardioverter defibrillator (ICD) lead revisions and extractions is steadily increasing. Despite the lack of representative studies, the risk of lead extraction is frequently considered to be lower than leaving nonfunctional leads in situ.We report the case of a patient who was referred to our institution for exchange of a malfunctioning ICD lead. The diagnostic work-up revealed a long-segment transmural migration of the ICD lead at the site of the subclavian and innominate vein. Due to the unpredictable risk of vein perforation, we abandoned the extraction procedure.
Keywords: implantable cardioverter defibrillator; lead extraction; transmural migration